Clinical implications of SCN1A missense and truncation variants in a large Japanese cohort with Dravet syndrome. (24th December 2016) - Ishii, Atsushi; Watkins, Joseph C.; Chen, Debbie; Hirose, Shinichi; Hammer, Michael F.
Summary: Objective: Two major classes of SCN1A variants are associated with Dravet syndrome (DS): those that result in haploinsufficiency (truncating) and those that result in an amino acid substitution (missense). The aim of this retrospective study was to describe the first large cohort of Japanese patients with SCN1A mutation–positive DS (n = 285), and investigate the relationship between variant (type and position) and clinical expression and response to treatment. Methods: We sequenced all exons and intron–exon boundaries of SCN1A in our cohort, investigated differences in the distribution of truncating and missense variants, tested for associations between variant type and phenotype, and compared these patterns with those of cohorts with milder epilepsy and healthy individuals. Results: Unlike truncation variants, missense variants are found at higher density in the S4 voltage sensor and pore loops and at lower density in the domain I–II and II–III linkers and the first three segments of domain II. Relative to healthy individuals, there is an increased frequency of truncating (but not missense) variants in the noncoding C‐terminus. The rate of cognitive decline is more rapid for patients with truncation variants regardless of age at seizure onset, whereas age at onset is a predictor of the rate of cognitive decline for patients with missense variants. Significance: We found significant differences in the distribution of truncating and missense variants across the SCN1A sequence among healthy individuals, patients with DS, and those with milder forms of SCN1A ‐variant positive epilepsy. Testing for associations with phenotype revealed that variant type can be predictive of rate of cognitive decline. Analysis of descriptive medication data suggests that in addition to conventional drug therapy in DS, bromide, clonazepam and topiramate may reduce seizure frequency.